The Impact of Activity Based Learning on Students’ Achievement. A study Among 12 Grade Science and Environment Student in a public School in Oman - ALBADI, AHMED (2019)
In recent years, there has been an ongoing debate about the impacts of using activity based learning strategies instead of traditional learning strategies in the classroom, what is more appropriate to increase student’s motivation and attainment. The purpose of this study was to determine the influence of activity based learning on students’ achievement in comparison to passive learning and detect students’ views towards activities. A study conducted in a public school in Oman. For this purpose, mixed research method was utilized. Quasi-experimental research design with pre-test and post-test was used in the research. Sample of this study include 24 twelve grade male students. They were divided into two groups control and experimental group. The first group received traditional learning and the second group was taught through activity based learning strategy. After that, focus group interviews were hold with 8 participants from experimental group for the qualitative data. Independent sample t-test was used for analysing the quantitative data, whereas content analysis technique was implemented for the qualitative finding. The result of the study indicated that activity based learning had a positive effect on students’ achievement. Students believe that activity based learning enhance understanding, increase a sense of responsibility, create attractive learning environment and increase achievement.